Vegetation Structure and Species Composition Inside the Habitat of Critically Endangered White-bellied Heron (Ardea insignis Hume, 1878) Along the Phochu in Punakha district, Bhutan - Rabten; Ugyen Dorji; Jigme Tenzin (CV. Literasi Indonesia, 2022)
Floristic compositions and vegetative structures are key determinants for selecting nests and roosting habitats of Critically Endangered White-bellied Heron. However, none of the Bhutanese researchers had ever studied to date. Gradient-directed transect methods were adopted using systematic sampling. Vegetation surveys were carried out inside 10 x 10 m (trees), 5 x 5 m (shrubs), and 2 x 2 m (herbs) in 48 plots across the Pochu landscape. The result shows that the Phochu landscape recorded 10 trees species belonging to six families. Pinus roxburghii is the most dominant species with relative density [RD] (86.77%), relative frequency [RF] (37.50%), relative dominance [RD] (79.93%), and IVI (204.20). While, L. ovalifolia and A. lebbeck were the lowest (RD (0.53%), RF (6.25%), RD (0.07%), (0.83%), IVI (6.85), and 7.61 respectively. While shrub constitutes 19 species and belongs to 14 families. Chromolaena odorata (32.15%, n = 933) and Cymbopogon sp. (21.26%, n = 617) were the most dominant herbs, while, Galium aparine (0.03%, n = 1) were lowest with 38 herbs species belongs to 20 families. For vegetative structures, maximum trees (38.62%, n = 73) DBH ranges from the 11-15 cm, which are found in day roosting site 1 (34.25%, n = 25). While, lowest ((0.53%, n = 1) was DBH ranges of 51-55 cm, 61-65 cm, 66-70 cm and 71-72 cm respectively. Therefore, similar vegetation composition and structure studies are suggested in other core habitats across Bhutan to deduce its habitat ecology for the long-term conservation of Critically Endangered WBH in Bhutan.